Postcolonial criticism in Sabah: A review / Jenna Desiree Robert - Robert, Jenna Desiree (Universiti Teknologi MARA, Sabah, 2021)
Sabah, formerly known as North Borneo during the period of British colonisation from 1888-1963 produced many texts about the British presence and their activities on the island. This review highlights that the post-war studies especially Sabah’s colonial literature is the missing link to its alternative history. Colonial literature has left its legacy in the form of history, anthropology and art but also in the textual and literary representations of Sabah through a western lens. The critique of colonial fiction and non-fiction texts in former colonies in Malaya and Sarawak have paved the way for critical examination and commentary on the modes of representation of the indigenous and immigrants. This review discusses the highlights of postcolonial criticism in Malaysia. It briefly introduces some of the issues about postcolonial criticism in Sabah and its potential.